Imaging cognitive and behavioral symptoms in Parkinson's disease. (December 2010) - Antonelli, Francesca; Ray, Nicola; Strafella, Antonio P
Non-motor symptoms are a major and often unrecognized cause of morbidity of Parkinson's disease. In the past few years, imaging technology, such as functional MRI and PET, have provided a large bulk of information about the phenomena. Here, we provide an overview of those imaging studies that may help us understand the neuronal correlates associated with non-motor symptoms in Parkinson's disease, with a particular focus on cognitive and neuropsychiatric deficits.